1991
DOI: 10.1113/jphysiol.1991.sp018666
|View full text |Cite
|
Sign up to set email alerts
|

Uneven distribution of excitatory amino acid receptors on ventral horn neurones of newborn rat spinal cord.

Abstract: SUMMARY1. The distribution of excitatory amino acid receptors on ventral horn neurones was investigated using slices of newborn rat spinal cord.2. The neurone and the tip of the pipette used to inject amino acids were visualized using Lucifer Yellow under a fluorescent microscope. The pipette was precisely located on the soma and dendrite of the neurone under visual control, and L-glutamate (Glu), L-aspartate (Asp), N-methyl-D-aspartate (NMDA), kainate (KA) and quisqualate (Quis) were ionophoretically applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Also, in spinal neurons recorded in vivo and in vitro , glutamate applications to dendritic sites proved to be more effective than to the soma. (Zieglgänsberger & Champagnat 1979;Onodera & Takeuchi 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Also, in spinal neurons recorded in vivo and in vitro , glutamate applications to dendritic sites proved to be more effective than to the soma. (Zieglgänsberger & Champagnat 1979;Onodera & Takeuchi 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The NMDA/AMPA ratio was positively correlated with RI (r ϭ 0.51; p Ͻ 0.01), although some neurons exhibiting RI Ͻ 1 had high NMDA/AMPA ratios. Previous studies on cerebral and hippocampal pyramidal neurons and spinal cord neurons have shown that the expression of NMDA receptors is constant or decreases from the soma to the dendrites, but the expression of AMPA receptors in the soma is lower than in the dendrites (Onodera and Takeuchi, 1991;Dodt et al, 1998;Andrasfalvy and Magee, 2001). If the distribution of AMPA and NMDA receptors at the somatic-dendritic membrane in PHN neurons is similar to that in pyramidal and spinal neurons, the NMDA/AMPA ratio measured at the soma of PHN neurons may actually be smaller at synaptic sites presumably located at the dendrites.…”
Section: Expression Of Ca 2؉ -Permeable Ampa Receptors In Phn Neuronsmentioning
confidence: 92%
“…: <10 ms; Mayer et al, 1991) and complete recovery from desensitization after short pulse ejection of glutamate onto motoneurones, comparable to the synaptic release, takes more than 1 s. (Onodera & Takeuchi, 1991). On the other hand, the onset (Onodera & Takeuchi, 1991) and the desensitization kinetics of NMDA receptors is slower and lesser in degree (time const. : t 300ms, Mayer et al, 1991).…”
Section: Discussionmentioning
confidence: 99%